SO ORDERED: A Textual Analysis of United States’ Governors’ Press Release Responses to the COVID-19 Pandemic (Journal of International Crisis and Risk Communication Research, 2021)
The COVID-19 pandemic presents a unique environment from which each individual state, in the United States, has been forced to address their publics. In order to understand how each state has engaged with this pandemic, a textual analysis of each state’s governor’s first press release was conducted; five thematic trends were identified. Through use of the social trust approach to risk communication and the contingency theory of strategic conflict management (using external threat variables), the implications of these press releases are discussed.